CONTESTED TERRITORY OF ARCHITECTURAL THEORY - Haddad, Elie ([S.l.] : ROUTLEDGE, 2022)
This book brings together a diverse group of theoreticians to explore architectural theory as a discipline, assessing its condition and relevance to contemporary practice. Offering critical assessment in the face of major social and environmental issues of today, 17 original contributions address the relevance of architectural theory in the contemporary world from various perspectives, including but not limited to: politics, gender, representation, race, environmental crisis, and history. The chapters are grouped into two distinct sections: the first section explores various historical perspectives on architectural theory, mapping theory's historiographical turn and its emergence and decline from the 1960s to the present; the second offers alternative visions and new directions for architectural theory, incorporating feminist and human rights perspectives, and addressing contemporary issues such as Artificial Intelligence and the Age of Acceleration. This edited collection features contributions from renowned scholars as well as emergent voices, with a Foreword by David Leatherbarrow. This book will be of great interest to graduate and upper-level students of architecture, as well as academics and practicing architects.
Keywords: ARCHITECTURE / Criticism; Architecture -- Philosophy